Scavenging of 230Th in the Sulu Sea - Okubo, Ayako; Obata, Hajime; Gamo, Toshitaka; Minami, Hideki; Yamada, Masatoshi (Deep-sea research. Part II, Topical studies in oceanography, 2007)
Thorium-230 concentrations were determined in the Sulu Sea, a small 5000 m deep basin surrounded by the Philippine and Malaysian Islands, and the South China Sea. The mid-water of South China Sea flows into the Sulu Sea through the Mindoro Strait (sill depth 420 m). Thorium-230 concentrations in deep waters at two stations (PA-1 in the Sulu Sea and PA-11 in the South China Sea) are considerably lower than those in the open ocean (average concentrations below sill depth: 0.49 dpm/m 3 (PA-1), 0.79 dpm/m 3 (PA-11)). The low concentration and homogeneity of 230Th in deep water below sill depth are consistent with the trend of other semi-closed basins such as the Japan Sea. We also measured 232Th concentration in the Sulu Sea. From these data, terrigenous 230Th was calculated to be 19% of the measured 230Th in the basin. The most probable explanation for the 230Th deficit in the deep water of the Sulu Sea is an enhanced scavenging effect by the particles supplied from the seafloor. Using a simple box model, the amount of 230Th scavenged by particles supplied from the seafloor is calculated to be 0.052 dpm/m 3/y.